Along the Indian Highway: an ethnography of an international travelling exhibition - Bublatzky, Cathrine (Routledge, 2019)
Along the Indian Highway : an introduction -- 'Cancel that flight to Delhi' : Serpentine Gallery, London 2008 -- 'Indianness and the urgency of transmission' : Astrup Fearnley Museum, Oslo 2009 -- 'There might be an Indian background, but the theme is global' : Heart Museum Of Contemporary Art, Herning 2010 -- Transcultural dissonances in the contemporary art world : Museo nazionale delle arti del XXI secolo, Rome 2012 -- Indian Highway VI finally on its way to China : Ullens Centre for Contemporary Art, Beijing 2012 -- Shared exoticisms or the limits of the national exhibition : some final observations.
Keywords: Indian Highway (Exhibition); Kunstausstellung; Indienbild; Exhibition Indian Highway